Medicinal plants utilized for fitness disorders treatment by ethnic groups in Papua and West Papua Province, Indonesia - Dian Susanti, Nuning Rahmawati, Ika Yanti M. Sholikhah, Rohmat Mujahid, Dyah Subositi, Harto Widodo, Yuli Widiyastuti, Sari Haryanti (Journal of Applied Pharmaceutical Science, 2023)
Papua is one of Indonesia’s islands with a large biological wealth, including medicinal plants. This study aimed to identify the utilization of medicinal plants by selected traditional healers who met inclusion criteria to treat fitness disorders in ethnic groups of Papua and West Papua. Data was collected through interviews, observation, and sample collection. Data quantification was done by analyzing the use value parameters, simple preference ranking exercise, multi-health purpose species rank, and the plant parts value. This study revealed 43 concoction information details and identified the use of 24 plant species distributed in 19 families among 19 healers in 10 ethnic groups in Papua and West Papua. Cymbopogon citratus (DC.) Stapf (12.12%) and leaves (57.35%) were determined as the most prominent species and plant parts used. Morinda citrifolia was identified as the species with the biggest number of other treatable diseases, with a total score of 85. The most used plant families were Myrtaceae and Poaceae, each with a percentage of 12.12%. The study showed the critical role of medicinal plants and traditional healers in community health. However, conservation efforts must be initiated immediately since almost 40% of traditional healers still harvest the available plants and make no cultivation efforts.
Keywords: Medicinal plant, Papua, fitness disorders, traditional healer, Cymbopogon citratus